2012
DOI: 10.1007/s00384-012-1621-5
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial embolization in acute colonic bleeding: review of 11 years of experience and long-term results

Abstract: Background Lower gastrointestinal bleeding represents 20 % of all gastrointestinal bleedings. Interventional radiology has transformed the treatment of this pathology, but the long-term outcome after selective embolization has been poorly evaluated. The aim of this study is thus to evaluate the short-term and long-term outcomes after selective embolization for colonic bleeding.Methods From November 1998 to December 2010, all acute colonic embolizations for hemorrhage were retrospectively reviewed and analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
2
8
0
2
Order By: Relevance
“…We did, however, encounter one patient who had asymptomatic ischaemia noted on a follow-up colonoscopy prior to an elective bowel resection. Given that the rates of ischaemic events in past studies using endovascular technique with various embolic agents have been reported in the range of 3-21%, 4,16,27,28 our experience provides validation to the idea that the risk of ischaemia is lower with coils than with the other agents used for treatment (i.e. particulates, gelatin sponge and n-BCA liquid embolic).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We did, however, encounter one patient who had asymptomatic ischaemia noted on a follow-up colonoscopy prior to an elective bowel resection. Given that the rates of ischaemic events in past studies using endovascular technique with various embolic agents have been reported in the range of 3-21%, 4,16,27,28 our experience provides validation to the idea that the risk of ischaemia is lower with coils than with the other agents used for treatment (i.e. particulates, gelatin sponge and n-BCA liquid embolic).…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, prior published data on endovascular technique is limited by a majority of studies using a combination of different embolic agents to manage lower GI bleeding, consequently confounding the evaluation for efficacy of any one single agent. 4,[11][12][13][14][15][17][18][19]25,27,28 The present study sought to address this concern by examining both early and delayed rebleeding rates in patients managed specifically by superselective microcoil embolization, yielding rates of 11.5% and 15.3%, respectively. These findings take an initial step at showing the ability to achieve long-term haemostasis in most patients treated by endovascular coiling alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings complement those of a recent study providing additional insights into the short-term outcomes of angiographic therapy and subsequent embolization in patients with GIB. [11][12][13] Management options for patients with acute nonvariceal upper GIB that does not respond to initial endoscopic treatment include repeat endoscopy, emergency surgery, and angiographic embolization. Several studies have compared the effectiveness of surgery to embolization in treating patients with GIB.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric angiography and embolization is both diagnostic and therapeutic. There is a risk of bowel ischemia (16.7% in one study) from the procedure as well as the possibility of renal failure and contrast reactions in select patient populations [9]. Endoscopy can also be diagnostic through direct visualization and therapeutic with epinephrine injection, cauterization, or vessel clipping.…”
Section: Discussionmentioning
confidence: 99%